Urang Banjar dan Tarekat Sammaniyah di Banua Urang: Sebuah Penelusuran Awal di Serdang Bedagai, Sumatera Utara - Bakar, Abu; Prayogo, Imam (Sekolah Tinggi Agama Islam Sumatera Medan, 2023)
: This research analyzes Urang Banjar in banua urang (Serdang Bedagai Regency) with a focus on analyzing the identity and existence of Urang Banjar in Serdang Bedagai, their religious traditions, the existence of Tarekat Sammaniyah that they follow, and the spiritual value in the practice of Tarekat Sammaniyah that they do. This research asks the question what are the spiritual elements and how do they affect Urang Banjar in Serdang Bedagai. To answer the research questions, qualitative research was chosen as a type of research that seeks to present data sourced from the object under study. The approach used is ethnography which focuses on Urang Banjar in Serdang Bedagai. Data collection techniques used observation, interviews and documentation studies. The research findings show that the spiritual elements that develop in the Banjar community in Serdang Bedagai are sourced from the Sammaniyah Order which originated from their homeland in Kalimantan. This research confirms that there is an influence of Tarekat Sammaniyah in the religious and social aspects of the community, namely Urang Banjar and Tarekat Sammaniyah have merged in the form of traditions that develop in the community in Serdang Bedai. The results of this research have implications for the addition of Islamic scholarship, as well as showing the development of Islam in the country.